Exploring the standardized detection and sampling methods of human nasal SARS-CoV-2 RBD IgA - Xuanxuan Zhang; Xuanxuan Zhang; Jizong Jia; Chaoying Hu; Chaoying Hu; Yulong Fu; Guanxing Liu; Yajing Li; Qian He; Qian He; Fan Gao; Fan Gao; et al. (Frontiers in Immunology)
IntroductionVaccines capable of effectively inducing mucosal immunity, particularly specific IgA antibodies, represent an ideal strategy for preventing infections and the transmission of pathogens such as SARS-CoV-2 and influenza viruses that rapidly replicate in the upper respiratory tract and cause clinical symptoms. However, a lack of standardized nasal antibody detection and sampling methods has hindered cross-study comparability and vaccine development.MethodsThis study uses SARS-CoV-2 as a model pathogen to standardize nasal antibody detection methods and sampling methods. Following the scientific guidelines (Q14 and Q2(R2)) for analytical procedure development and validation released by the International Council for Harmonization (ICH), an ELISA for nasal SARS-CoV-2 WT-RBD specific IgA detection was established and validated. To compare the sampling methods, nasal samples were collected from five groups using three commonly used nasal sampling methods (M1: nasopharyngeal swab; M2: nasal swab; M3: expanding sponge method). The total IgA and SARS-CoV-2 WT-RBD IgA in clinical samples were detected.ResultsThe first validated ELISA for nasal SARS-CoV-2 WT-RBD specific IgA detection was established through analytical target profiling (ATP), risk assessment, and design of experiment optimization. Systematic validation demonstrated exclusive specificity for the target antigen, with intermediate precision of <17% and relative bias of <±4%, meeting ATP requirements. Analysis of 154 clinical samples demonstrated strong concordance between the novel method and electrochemiluminescence assays, with a concordance correlation coefficient of 0.87 for quantitative results and a kappa coefficient of 0.85 for results above and below the dilution-adjusted limit of quantification (LOQ). Applying this novel method, a clinical comparison revealed that M3 achieved superior performance in terms of the single-day detection rate (above dilution-adjusted LOQ 95.5%), 5-day consecutive detection rate (above dilution-adjusted LOQ 88.9%), and median SARS-CoV-2 WT-RBD IgA concentration (171.2 U/mL), significantly outperforming M1 (68.8%; 48.7%; 28.7 U/mL, p<0.0001) and M2 (88.3%; 77.3%; 93.7 U/mL, p<0.05).ConclusionThis study has established the first standardized nasal detection system. The system can be adapted with appropriate modifications for the clinical evaluation of other respiratory mucosal vaccines, thereby advancing the development of mucosal vaccines.